Expansion of human mesenchymal stem/stromal cells on temporary liquid microcarriers - Hanga, Mariana P (J Chem Technol Biotechnol, 2020)
BACKGROUND: Traditional large‐scale culture systems for human mesenchymal stem/stromal cells (hMSCs) use solid microcarriers as attachment substrates. Although the use of such substrates is advantageous because of the high surface‐to‐volume ratio, cell harvest from the same substrates is a challenge as it requires enzymatic treatment, often combined with agitation. Here, we investigated a two‐phase system for expansion and non‐enzymatic recovery of hMSCs. Perfluorocarbon droplets were dispersed in a protein‐rich growth medium and were used as temporary liquid microcarriers for hMSC culture. RESULTS: hMSCs successfully attached to these liquid microcarriers, exhibiting similar morphologies to those cultured on solid ones. Fold increases of 3.03 ± 0.98 (hMSC1) and 3.81 ± 0.29 (hMSC2) were achieved on day 9. However, the maximum expansion folds were recorded on day 4 (4.79 ± 0.47 (hMSC1) and 4.856 ± 0.7 (hMSC2)). This decrease was caused by cell aggregation upon reaching confluency due to the contraction of the interface between the two phases. Cell quality, as assessed by differentiation, cell surface marker expression and clonogenic ability, was retained post expansion on the liquid microcarriers. Cell harvesting was achieved non‐enzymatically in two steps: first by inducing droplet coalescence and then aspirating the interface. Quality characteristics of hMSCs continued to be retained even after inducing droplet coalescence. CONCLUSION: The prospect of a temporary microcarrier that can be used to expand cells and then ‘disappear’ for cell release without using proteolytic enzymes is a very exciting one. Here, we have demonstrated that hMSCs can attach and proliferate on these perfluorocarbon liquid microcarriers while, very importantly, retaining their quality.